Просторова структура Луцька наприкінці XVIII – у середині ХІХ ст. - Карліна, Оксана Миколаївна; Karlina, Oksana (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті на основі мікростатистичного аналізу клірових відомостей показано задіяність волинських єреїв у роботі єпархіального управлінського апарату та виконання ними архієрейських доручень у першій половині ХІХ ст. Схарактеризовано устрій органів управління Православної церкви на Волині у визначений період.We consider the spatial structure of Lutsk late XVIII - mid ХІХ century. It includes the types and functions of the building, transport network, etc. settling characteristics. In the Russian Empire for a long time Luck got humble status of the district center in southwestern outskirts of the state, which could not affect its development. By the end of 1860 the city developed without the use of a predefined plan according to the relief features, so its buildings characterized chaotic and disordering. On the one hand, compressed urban space through intensive use of the island territory of Lutsk, on the other hand, expanded by building and joining suburban settlements.
The Spatial Structure of Lutsk late XVIII – Mid ХІХ Century
Keywords: Волинська єпархія; клірові відомості; духовна консисторія; духовне правління; благочиння; Volyn province; Luck; spatial structure; urban development; plan of the city